Metallophthalocyanine derivatives as catalysts for the detection of sulphur dioxide, cyanide, nitrite and amino acids - Thamae, Mamothibe Amelia (Rhodes University, Faculty of Science, Department of Chemistry, 2003)
Electrocatalytic reduction and oxidation of nitrite using cobalt phthalocyanine derivatives was studied. The detection limit of 1 x 10â »Â¹Â° mol dmâ »Â³ was achieved when these molecules were employed as catalysts for nitrite detection. The mechanisms for nitrite catalysis were proposed. The position of the peripheral substituents on cobalt porphyrazines (related to cobalt phthalocyanines) affected the catalytic activity of these complexes. The highest activity for nitrite reduction was observed on the cobalt(II) 2,3-tetramethyltetrapyridinoporphyrazine ([CoTm-2,3-tppa]â ´â º), with cobalt phthalocyanine showing the lowest activity, and the cobalt(II) 3,4- tetramethyltetrapyridinoporphyrazine ([CoTm-3,4-tppa]â ´â º), showing intermediate behaviour. A mixture of a negatively charged cobalt(II) tetrasulfophthalocyanine ([CoÂ¹Â¹TSPc]â ´â ») and a positively charged [CoTm-3,4-tppa]â ´â º showed better activity for nitrite reduction than did the individual components. Cobalt porphyrazines lowered the potentials for nitrite reduction in that peaking was observed, as opposed to cobalt phthalocyanine, where only the increase in currents was observed without peaking. Using the cobalt phthalocyanine derivatives, nitrite can be reduced to ammonia with high current efficiency. A glassy carbon electrode modified with [CoÂ¹Â¹TSPc]â ´â » was employed for the determination of nitrite. Nitrate had an insignificant effect on nitrite oxidation on these modified electrodes. Electrocatalytic determination of S0â‚‚ was studied as a function of pH at a glassy carbon electrode modified with iron(II) tetrasulfophthalocaynine. It was found that depending on pH, S0â‚‚.xHâ‚‚0, HS0â‚ƒâ » and/or SOâ‚ƒÂ²â » are the main compounds in solution and that these compounds behave differently at the electrode surface. Detection limits ranging from 4.0 Â± 0.1 x 10â »â µ to 7.5 Â± 0.1 x 10â »â µ mol dmâ »Â³ depending on pH were observed. Similar results were obtained when cobalt(II) tetrasulfophthalocaynine was employed for S0â‚‚ catalysis under the same experimental conditions. Cysteine and histidine determination using oxidation currents was performed on glassy carbon electrodes modified with [CoTm-3,4-tppa]â ´â º (represented as [CoTm-3,4-tppa]â ´â º-GCE) in pH 7 Tris buffer. The detection limit of 1.0 x 10â »â µ mol dmâ »Â³ for cysteine and 2.24 x 10â »â · mol dmâ »Â³ for histidine were obtained. Cyanide can be detected down to 1 x 10â »Â¹Â¹ mol dmâ »Â³ using [CoTm-3,4-tppa]â ´â º-GCE in pH 10.8 buffer. Cyanide and S0â‚‚ coordinate to the [CoTSPc]â ´â » species. The coordination is accompanied by oxidation of the central Co(II) metal, forming a [CoÂ¹Â¹Â¹CoTSPc]Â³â » species. The rate constants for cyanide coordination to the [CoÂ¹Â¹TSPc]â ´â » complex are larger than those reported for the coordination of cyanide to FePc and RuPc complexes in non-aqueous media. Autoreduction of [CoÂ¹Â¹Tmtppa]â ´â º occurred in the presence of either histidine or cysteine, with the formation of metal reduced species, [CoÂ¹Tmtppa(-2)]Â³â º. Nitric oxide and nitrite coordinate to the [CoÂ¹Â¹Tmtppa]â ´â º species, without auto-reduction of this species, which was observed for cysteine or histidine. The use of [CoÂ¹Â¹TSPc]â ´ resulted in improved rate of interaction with nitrite when compared to the [CoÂ¹Â¹Tmtppa]â ´â º species.
Keywords: Cyanides; Nitric oxide; Electrochemistry; Nitrites; Suplhur dioxide; Amino acids